Intensification of medication and glycaemic control among patients with type 2 diabetes – the ADVANCE trial. Issue 5 (16th December 2013) - van Dieren, S.; Kengne, A. P.; Chalmers, J.; Beulens, J. W. J.; Davis, T. M. E.; Fulcher, G.; Heller, S. R.; Patel, A.; Colagiuri, S.; Hamet, P.; Mancia, G.; Marre, M.; et al.
<x xml:space="preserve">Abstract</x> Aims The aim of this study was to assess associations between patient characteristics, intensification of blood glucose‐lowering treatment through oral glucose‐lowering therapy and/or insulin and effective glycaemic control in type 2 diabetes. Methods 11 140 patients from the Action in Diabetes and Vascular disease: preterAx and diamicroN‐MR Controlled Evaluation (ADVANCE) trial who were randomized to intensive glucose control or standard glucose control and followed up for a median of 5 years were categorized into two groups: effective glycaemic control [haemoglobin A1c (HbA1c) ≤ 7.0% or a proportionate reduction in HbA1c over 10%] or ineffective glycaemic control (HbA1c > 7.0% and a proportionate reduction in HbA1c less than or equal to 10%). Therapeutic intensification was defined as addition of an oral glucose‐lowering agent or commencement of insulin. Pooled logistic regression models examined the associations between patient factors, intensification and effective glycaemic control. Results A total of 7768 patients (69.7%), including 3198 in the standard treatment group achieved effective glycaemic control. Compared to patients with ineffective control, patients with effective glycaemic control had shorter duration of diabetes and lower HbA1c at baseline and at the time of treatment intensification. Treatment intensification with addition of an oral agent or commencement of insulin was associated with a 107% [odds ratio, OR: 2.07 (95% confidence interval, CI: 1.95–2.20)] and 152% [OR: 2.52 (95% CI: 2.30–2.77)] greater chance of achieving effective glycaemic control, respectively. These associations were robust after adjustment for several baseline characteristics and not modified by the number of oral medications taken at the time of treatment intensification. Conclusions Effective glycaemic control was associated with treatment intensification at lower HbA1c levels at all stages of the disease course and in both arms of the ADVANCE trial.